2016
DOI: 10.1186/s40409-016-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the in vivo wound healing effects of a recombinant hemolin from the caterpillar Lonomia obliqua

Abstract: BackgroundHemolin proteins are cell adhesion molecules from lepidopterans involved in a wide range of cell interactions concerning their adhesion properties. However, hemolin’s roles in cell proliferation and wound healing are not fully elucidated. It has been recently reported that rLosac, a recombinant hemolin from the caterpillar Lonomia obliqua, presents antiapoptotic activity and is capable of improving in vitro wound healing. Therefore, this study aimed to explore rLosac’s in vivo effects using a skin wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…To the best of our knowledge, this is the first report that rLosac and rLopap have the ability to stimulate a key process of skeletal muscle regeneration. The stimulatory effect of rLosac on myoblast proliferation is in line with previous reports that this protein promotes proliferation of human endothelial cells ( Bettencourt et al, 1997 ; Bettencourt et al, 1999 ; Alvarez Flores et al, 2006 ; Alvarez-Flores et al, 2011 ; Bosch et al, 2016 ; Sato et al, 2016 ; Alvarez-Flores et al, 2019 ). The protein was therefore indicated by these authors as a promising molecule for the development of new formulations for wound healing.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first report that rLosac and rLopap have the ability to stimulate a key process of skeletal muscle regeneration. The stimulatory effect of rLosac on myoblast proliferation is in line with previous reports that this protein promotes proliferation of human endothelial cells ( Bettencourt et al, 1997 ; Bettencourt et al, 1999 ; Alvarez Flores et al, 2006 ; Alvarez-Flores et al, 2011 ; Bosch et al, 2016 ; Sato et al, 2016 ; Alvarez-Flores et al, 2019 ). The protein was therefore indicated by these authors as a promising molecule for the development of new formulations for wound healing.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, the ability of the crude bristle extract of Lonomia obliqua to modulate inflammatory markers was recently demonstrated in a human macrophage model ( Oliveira et al, 2021 ). As Lopap has previously been shown not to exert pro-inflammatory activity ( Fritzen et al, 2005 ; Waismam et al, 2009 ) and, as with Losac, Lopap-derived peptides provide cytoprotective activity ( Chudzinski-Tavassi et al, 2010 ; Carrijo-Carvalho et al, 2012 ; Wlian et al, 2014 ; Alvarez-Flores et al, 2021 ) and improve wound healing ( Sato et al, 2016 ), we investigated the effect of these recombinant proteins in myoblast cells upon inflammatory stimulus by IL-1β. Interestingly, we found that both proteins exerted anti-inflammatory effects: they were able to inhibit the production of PGE 2 and IL-6 induced by IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caterpillars from different South American countries, such as Venezuela, Brazil, French Guyana, Peru, Paraguay, Argentina and Colombia, are responsible for a severe bleeding syndrome in humans who touch their bristles (Arocha-Pinango and Guerrero, 2001). Lonomia obliqua is the main species of caterpillar found in Southern Brazil and its venom is comprised of molecules with antiviral, procoagulant, fibrinolytic and wound healing activities (Veiga et al, 2005;Reis et al, 2006;Alvarez-Flores et al, 2011;Carmo et al, 2015;Sato et al, 2016). Their toxic compounds are found in the bristle extract, hemolymph, cryosecretion (a crude venomous fluid ejected by the whole secretory tegument of caterpillars, stored at -20°C for 24 h) and tegument extract (Pinto et al, 2006;Veiga et al, 2009).…”
Section: Caterpillarsmentioning
confidence: 99%